2022
DOI: 10.1016/j.wjorl.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A critical readability and quality analysis of internet‐based patient information on neck dissections

Abstract: Objective Patients are increasingly turning to the Internet as a source of healthcare information. Given that neck dissection is a common procedure within the field of Otolaryngology ‐ Head and Neck Surgery, the aim of this study was to evaluate the quality and readability of online patient education materials on neck dissection. Methods A Google search was performed using the term “neck dissection.” The first 10 pages of a Google search using the term “neck dissection” were analyzed. The DISCERN instrument wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 46 publications
1
7
1
Order By: Relevance
“…This is consistent with the studies conducted by Lee et al [ 76 ] and Hong et al [ 77 ], who reported no correlation between readability and quality scores. However, this differs significantly from the study conducted by Grose et al [ 71 ] and Raja and Patel [ 78 ], who reported positive correlations between DISCERN, FRES, and FKG, and therefore suggested that higher-quality websites are often more reliable and more likely to be readable. Thus, a more exhaustive investigation of the correlation between FKG, FRES, and DISCERN is required.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the studies conducted by Lee et al [ 76 ] and Hong et al [ 77 ], who reported no correlation between readability and quality scores. However, this differs significantly from the study conducted by Grose et al [ 71 ] and Raja and Patel [ 78 ], who reported positive correlations between DISCERN, FRES, and FKG, and therefore suggested that higher-quality websites are often more reliable and more likely to be readable. Thus, a more exhaustive investigation of the correlation between FKG, FRES, and DISCERN is required.…”
Section: Discussioncontrasting
confidence: 99%
“…Only 9% (5/57) of the websites achieved the recommended sixth grade or lower readability level. This is similar to observations by McKearney and McKearney [ 70 ] and Grose et al [ 71 ], who both reported an average reading level of 10th grade on websites discussing ear tubes and neck dissections, respectively. Websites with information with a reading grade higher than the recommended level were also reported by Raja and Fitzpatrick [ 29 ], De La Chapa et al [ 72 ], Crabtree and Lee [ 3 ], and Kim et al [ 73 ], thus demonstrating the poor readability of health care websites in general.…”
Section: Discussionsupporting
confidence: 90%
“…The mean FKGL level reported in 13 studies ranged from grade 8.8 to 14.8. [13][14][15][16][17][19][20][21][41][42][43] Pooling the data from these studies revealed a weighted FKGL mean grade of 10.78 (95% CI, 9.92-11.72), a weighted SMOG mean of 13.82 (95% CI, 12. 43-15.38), and a weighted FRE mean of 47.72 (95% CI, 41.94-54.31) (Figure 1).…”
Section: Readability Outcomesmentioning
confidence: 99%
“…43-15.38), and a weighted FRE mean of 47.72 (95% CI, 41.94-54.31) (Figure 1). 14,16,18,19,21,23,42,43 No studies reported a mean FKGL of grade 6. 42 The mean Coleman Liau index reported in 5 studies ranged between 10.0 and 12.8, while the reported mean SMOG score ranged between 10.6 and 16.0.…”
Section: Readability Outcomesmentioning
confidence: 99%
See 1 more Smart Citation